Profile of antiphospholipid antibodies and complement system in COVID-19 patients of different severity - N. V. Dolgushina; I. V. Menzhinskaya; O. S. Beznoshchenko; S. M. Mullabayeva; E. A. Gorodnova; L. V. Krechetova (Медицинская иммунология)
COVID-19, a severe acute respiratory syndrome caused by SARS-CoV-2, may predispose to thrombotic events, especially when combined with antiphospholipid antibodies (aPL). However, there are limited data on prevalence and antigenic specificity of aPL in COVID-19. Complement activation is assumed to play an important role in pathogenesis of COVID-19-associated coagulopathy. During the SARS-CoV-2 pandemic, it is necessary to identify important biomarkers for predicting severe course of COVID-19 and risk of thrombotic complications. Our objective was to evaluate the aPL profile, quantitative content and activity of complement and its components in COVID-19 patients graded by severity in the course of time. IgM and IgG antibodies to cardiolipin (CL), phosphatidylserine (PS), β2-glycoprotein-I (β2-GP-I), prothrombin (PT), annexin V (An V), as well as C1q complement component, content of its C3 and C4 components and total complement activity were determined in blood serum using ELISA approach. 141 patients with COVID-19 were included in the study. Group 1 consisted of 39 patients with mild form, group 2 (65 patients) presented with moderate form, and group 3 included 37 patients with severe form of COVID-19. Blood samples were obtained on day 3-7 of the disease (1st point) and after 14-28 days (2nd point). The results were as follows: aPL were detected in 29.1% of the total COVID-19 cohort, frequency of aPL detection by the severity grade did not differ (33.3%, 24.6% and 32.4%). In 8.5% of the patients, aPL were detected only at the 1st time point; in 14.2%, only at the 2nd point; and in 6.4% of the cases, at the both time points. Antibodies to PT (16.3%) and An V (11.3%) were revealed more frequently. The detection frequency of antibodies to PT was significantly higher than antibodies to CL and PS (7.1%), β2-GP-I (7.8%). The prevalence of aPL in groups 1 and 3 did not differ. At the 1st point in group 3, increased levels of C4 (89.2%) and C3 (24.3%) in blood, and a decrease in complement activity (35.1%) were more often observed than in group 1. At the 2nd time point in group 3, a decrease in complement activity was often detected (59.5%). The C3 levels exceeding 720 μg/ml were found to predict a 2.6-fold increased risk of severe COVID-19, and this risk became 3.3 times higher at C4 levels of > 740 μg/ml. The antibodies to PT and An V are often detected in COVID-19 patients, along with low prevalence of antibodies to CL and β2-GP-I. These antibodies can be involved in pathogenesis of COVID-19-associated coagulopathy, being detectable at the late stage of the disease, and they may trigger APS in predisposed patients and reconvalescents. Although presence of aPL antibodies is not associated with COVID-19 severity, their persistence over the period of convalescence may be an additional risk factor for thromboembolic complications. The COVID-19 patients are characterized by activation of the complement system, which increases in severe cases, and manifests with increased or decreased levels of C3 complement component, increased levels of C4 component in blood, and a decreased total complement activity. Quantitative determination of C3 and C4 complement components over the period of COVID-19 progression is of prognostic value, with respect to severity of the disease.